2019
DOI: 10.1177/0091415019836100
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Caution: An Examination of Age, Social Context, and Sex on Measures of Inhibitory Control and Risky Decision-Making

Abstract: Understanding how older adults successfully navigate complex choices like driving requires the consideration of processing speed, inhibitory control, attentional processes, and risk management, and the context within which these decisions occur. The current study employed the Flanker task, the Stoplight task, and a personality inventory with 43 younger adults and 49 older adults either while they were alone or being observed by two same-sex, similarly aged peers. On the Flanker task, older adults performed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…It follows, then, that younger adults would also be more likely to partake in highrisk behaviors. This is evidenced by the prevalence of risky behaviors such as drug abuse, crime, and risky sexual behavior seen in younger adults compared to their older adult counterparts (Cowell, Patiel, & Peters, 2019;Turner & McClure, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It follows, then, that younger adults would also be more likely to partake in highrisk behaviors. This is evidenced by the prevalence of risky behaviors such as drug abuse, crime, and risky sexual behavior seen in younger adults compared to their older adult counterparts (Cowell, Patiel, & Peters, 2019;Turner & McClure, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…High sensation seeking is associated with increased propensity toward risky behaviors that can be detrimental to oneself and others (Horvath & Zuckerman, 1993). Younger adults not only tend to have higher sensationseeking scores than older adults, but also demonstrate a greater inclination toward risky behaviors (Cowell, Patiel, & Peters, 2019;Turner & McClure, 2003). The present study considered whether risktaking behavior is a function of an overactive initiation system (a strong, immediate response to a stimulus) or an underactive inhibitory system (inability to resist an immediate response).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…toward risky behaviors that can be detrimental to oneself and others (Horvath & Zuckerman, 1993). Younger adults not only tend to have higher sensationseeking scores than older adults, but also demonstrate a greater inclination toward risky behaviors (Cowell, Patiel, & Peters, 2019;Turner & McClure, 2003). The present study considered whether risktaking behavior is a function of an overactive initiation system (a strong, immediate response to a stimulus) or an underactive inhibitory system (inability to resist an immediate response).…”
Section: Abstract High Sensation Seeking Is Associated With Increasementioning
confidence: 98%
“…Age-related differences in risky behavior were described in a number of studies, including financial games, as well as applied decision-making [34][35][36]. In the most of the studies risk-taking was reported to increase during aging, with elder adults being the most prone to risky decisions.…”
Section: Risk-taking Behaviormentioning
confidence: 99%